Advancing Indigenous futures with two-eyed seeing: Strategies for restoration and repair through collaborative research. Issue 1 (March 2023) - Smith, Carolyn; Diver, Sibyl; Reed, Ron
This article builds on the Indigenous research concept of two-eyed seeing, that is, learning from one eye with the strengths of Indigenous knowledges and ways of knowing, and from the other eye with the strengths of Western knowledges and ways of knowing. We do so by drawing on the authors' multiple standpoints (Karuk Tribal Member, Karuk Enrolled Descendent, and non-Indigenous ally) and experiences building longstanding research collaborations that apply biophysical science, ethnographic methods, and Karuk oral traditions to tribal lands protection. Using Kovach's conversational methodology, we discuss problems of health and well-being that arise from two-eyed seeing research collaborations affecting Indigenous lands, waters, and resources. We specifically examine interventions for advancing Indigenous leadership in research that intersect with the Karuk Tribe's ecocultural revitalization initiatives through (1) stewardship of baskets alongside basket-weaving communities (human and nonhuman); (2) family based management of ceremonial trails, and (3) allyship for tribal–academic collaborations. Our analysis emphasizes how the aliveness of Karuk knowledge resists ahistorical essentialism, for example, by engaging with the joy of human/nonhuman relations, ceremonial scale, and solidarity practices. Responding to ongoing challenges with knowledge hierarchies, this work recognizes the importance of mutual acknowledgment of persons across systems for advancing Indigenous research as a multi-vocal initiative with the capacity for restoration and repair.